Hematological indices in the adult saudi population: Reference intervals by gender, age, and region - Shaheen, Naila A.; Rehan, Hina; Moghairi, Areej; Gmati, Giamal; Damlaj, Moussab; Salama, Hind; Rather, Mushtaq; Mendoza, May Anne; Alanazi, Abeer; Al Ahmari, Bader; Al Zahrani, Mohsen; Al-Hejazi, Ayman; et al. (Frontiers in Medicine, 2022)
Introduction Hematological parameters are critical in disease diagnosis, management and monitoring; however, complete blood count (CBC) reference intervals vary across populations. The aim of the current study was to provide the reference ranges of hematological parameters/indices in the healthy adult Saudi population. Methods A multicenter retrospective cross-sectional study was conducted with a sample of employees who were screened pre-employment from January 2015 to December 2019, at tertiary care hospitals in three regions. Demographic and CBC data were extracted from the electronic health system. The 2.5th and 97.5th percentiles were used to determine the reference intervals. Results Of a total of 1,388 participants, 53.82% were male. The majority (96%) were less than 40 years old, and 85% were from the Central region. Gender related differences were observed for the RBC count, Hb, HCT, MCV, MCH, MCHC, and the platelet count. Age related differences were observed for the RBC, Hb, HCT, and eosinophils. The WBC parameters did not differ by gender or age categories. Region related differences were observed for the RBC, hemoglobin, HCT, MCV, WBC, and basophils. The platelet count was higher in the female group, the age group 40 years and above, and in the Western region. The prevalence of anemia was high in the female group and the Eastern region. The overall neutropenia rate was 12.8%. Conclusion The data from this study provides hematological parameter reference ranges for the adult Saudi population by gender, age, and region. Gender and age-related differences were observed for the hematological parameters. Anemia was more frequent in the female group and the Eastern region. Caution must be taken when comparing or interpreting results from different age groups, gender, region of origin, and ethnicity.